STRATEGI PEMASARAN JASA DALAM KONTEKS PENDIDIKAN DALAM MENINGKATKAN DAYA SAING DAN KEPUASAN PELANGGAN - Muhamad Fadholi; Siti Zulaikha; Siti Rochanah; Rika Karilia; Muhammad Fitri (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
Service marketing strategy is the main aspect that needs to be explored to identify potential for improvement and development. This research discusses formulating marketing strategies that will be implemented, analyzing student preferences and needs, and evaluating customer satisfaction. The results obtained are Analysis of Student Preferences: Students from the FIP UNJ Education Management Study Program prefer face-to-face learning methods (78.3%), although a small number also support blended learning; Various digital learning media have been used, showing readiness for further technology integration; Students need additional support such as tutors and workshops for their personal development. Satisfaction Level: Student satisfaction with various aspects such as lecturers, curriculum, campus facilities, and administrative services varies, with some areas requiring improvement, particularly in campus infrastructure and teaching quality. Recommended Marketing Strategy: Strengthening academic branding by highlighting alumni successes and improving teaching quality; Utilization of digital technology for learning and communication with students; Improvement of campus facilities to support offline learning and student comfort; Promotions and digital marketing campaigns to attract prospective new students. Conclusions and Suggestions: There is a need to improve the quality of teaching and campus facilities, optimize technology in learning, as well as more aggressive marketing campaigns to strengthen the competitiveness of study programs; Adapting the curriculum to industry needs is also important to ensure graduates remain competitive in the job market.